2019
DOI: 10.1186/s12877-019-1047-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SENATOR (Software ENgine for the Assessment and optimisation of drug and non-drug Therapy in Older peRsons) on incident adverse drug reactions (ADRs) in an older hospital cohort – Trial Protocol

Abstract: Background: The aim of this trial is to evaluate the effect of SENATOR software on incident, adverse drug reactions (ADRs) in older, multimorbid, hospitalized patients. The SENATOR software produces a report designed to optimize older patients' current prescriptions by applying the published STOPP and START criteria, highlighting drug-drug and drug-disease interactions and providing non-pharmacological recommendations aimed at reducing the risk of incident delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
1
18
0
6
Order By: Relevance
“…Classifying the identified cases of PPOs into drug classes in this study demonstrated that the most common drug classes associated with identified PPO cases involved vaccines, ACEIs, antiplatelets, statins, and vitamin D/calcium supplements. The findings of the present study were similar to results that were reported by other published studies (Gallagher et al, 2011;Frankenthal et al, 2013;Liu et al, 2012;Ryan et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Classifying the identified cases of PPOs into drug classes in this study demonstrated that the most common drug classes associated with identified PPO cases involved vaccines, ACEIs, antiplatelets, statins, and vitamin D/calcium supplements. The findings of the present study were similar to results that were reported by other published studies (Gallagher et al, 2011;Frankenthal et al, 2013;Liu et al, 2012;Ryan et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Future research examining the impact of softwaregenerated START criteria on drug-related hospitalizations and quality of life is needed for implementing medication prescription in day-to-day practice, bearing in mind that such criteria cannot replace clinical judgment. A recent first clinical trial to examine the effectiveness of a software intervention on incidental adverse drug reactions and associated healthcare costs during hospitalization for older patients with polypharmacy and comorbidities is ongoing (Lavan et al, 2019). On the contrary, other researchers claimed that the application of such software did not reduce adverse drug reaction incidence during hospitalization (O'Mahony et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These adjustments will, in turn, significantly reduce ADR incidence in intervention arm patients compared to matched patients receiving standard pharmaceutical care in the same medical centre. Further details are provided in a previous trial protocol paper 34 and are summarized in the Supplementary Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…By applying the STOPP and START criteria, the software produces a report which outlines possible drug-drug and drug-disease interactions and provides non-pharmacological recommendations aimed at reducing the risk of incident delirium. The primary endpoint of the study was to evaluate the percentage of patients with at least one probable or certain ADR occurring within 14 days of enrolment during the hospitalization period [74][75][76]. Unfortunately, the trial failed to show a significant impact in reducing the incidence of ADRs and the level of adherence by medical staff to the intervention was relatively low [77].…”
Section: Softwarementioning
confidence: 99%